The impact of an educational program on HCV patient outcomes using boceprevir in community practices (OPTIMAL trial). (September 2015) - Poordad, Fred; Rustgi, Vinod; Brown, Robert S.; Patel, Vishal; Kugelmas, Marcelo; Regenstein, Fredric; Balart, Luis; LaBrecque, Douglas; Brown, Kimberly; Avila, Mark; Biederman, Michael; Freed, Glenn; et al.
Objectives: Although effective, direct acting antiviral (DAA) therapies for genotype 1 (GT 1) hepatitis C virus (HCV) have been associated with compliance challenges. Additionally, treatment at predominantly community-based centers has been associated with low retention of patients on treatment and higher dropout rates. The OPTIMAL Phase IV interventional trial (ClinicalTrials.gov Identifier: NCT01405027) was designed to evaluate the impact of an education program for community investigator (CI) sites participating in a Chronic Liver Disease Foundation study treating chronic GT 1 HCV patients. Methods: This physician educational program was administered by 22 Hepatology Centers of Educational Expertise (HCEE) academic sites to 33 CI sites asked to participate from December 2011 to July 2012. The HCEE mentors from DAA-experienced academic sites educated those at CI sites on therapeutic management, practice, and patient outcomes through a series of four standardized educational sequence visits regarding the use of first generation HCV protease inhibitors and the overall treatment of HCV. Results: Treatment duration compliance rates for patients treated at CI sites versus those treated at HCEE academic sites were evaluable in 77 of 84 HCEE academic site patients, 102 of 113 patients treated at CI sites, and 179 of 197 overall patients. The treatment duration compliance rates for patients treated at HCEE academic sites, CI sites and overall were 85.4 ± 25.39%, 83.8 ± 27.37%, and 84.5 ± 26.48%, respectively, and did not differ statistically between the groups ( p = 0.49). Almost half (47%) of the patients in the study achieved a sustained virological response for 24 weeks (SVR24) regardless of the type of site ( p = 0.64). Safety profiles were similar at both HCEE and CI sites. Conclusions: These results demonstrated that education of CI sites unfamiliar with DAAs resulted in patient outcomes consistent with those observed at DAA-experienced academic sites.